Extended electronic and optical solutions for sensitive infrared photodetection - Pablo Nunes Agra Belmonte (2017)
This work aims to address the two main parts of an infrared photodetection system, which are the optics and the readout electronics. Also, an idealized example of a CO2 gas detection system is presented, in order to illustrate how the different parts should be coupled together in a practical application. The purpose of the readout electronics is to interface with a photodetector, reading out its input signal. However, since an infrared photodetector features low shunt resistance, large dark current, and large noise, it is not a trivial task for the readout electronics toproperly extract signal information from the detector. Therefore, especial circuits able to handle large input currents, and capable of tightly control the voltage bias across the detector are desired in this context. In addition, generally infrared readout circuits need to decrease the sensitivity of the detection system, so that larger currents can be properly read. This approach, however, usually decreases the Signal to Noise Ratio (SNR), especially for larger currents. Nonetheless, only a small portion of this current is related to the useful signal, and decreasing the SNR can mask this small current signal. Therefore, we present in this work a circuit, coined as the bouncing pixel, that presents a large charge storage capacity necessary to accommodate large currents, and yet with a very high sensitivity, being able to sense small differences in relatively high input currents. In fact, the SNR cannot increase above the SNR of the photodetector, that imposes the maximum limit. However, the larger the sensitivity, the closer the overall system SNR is to that of the detector. Also, a special version of the bouncing pixel is presented: the cascoded bouncing pixel. This circuit presents an even better performance, being suitable for infrared applications, mainly due to its ability of maintaining an even more stable voltage bias across the detector. The optical part of the system is comprised mainly by microlenses, that enhance the SNRof the system by strengthening the input optical signal. These lenses need to be transparent at the infrared range, and silicon proves to be a good choice, due to its low cost, low density, and relatively high refraction index. Therefore, it is a material suitable for lenses with very short focallength, allowing compact and light weighted systems. The silicon microlenses were fabricated using a process technique presented by de Lima Monteiro et al., 2003, that is less expensive than the conventional ones. The micromachined samples were also characterized, acquiringinformation of roughness and vergence of the lenses. In addition, a setup was assembled in order to measure the focal points of the samples, showing that the silicon wafers micromachined with the presented process actually behave as convex verging lenses. However, silicon features a high surface reflectance, and an anti-reflective coating needs to be deposited over the silicon surface, in order to maximize transmittance at the desired wavelength range. We have used theLPCVD deposited low stress Si rich nitride technique to deposit SiN layers of various thicknesses, and measured their transmittances. Very good transmittance profiles were found near 4.2 m (one of the wavelengths at which CO2 absorbs), although the optical constants dataset used for the SiN design simulations were not appropriate. Therefore, an updated fitting dataset wereextracted from measurements, allowing future designs with SiN aiming at different wavelengths(within a given range in the infrared) to be reliably simulated.At the end, both optical and electronic parts are coupled together in the idealized application of a CO2 gas detection system. A model was implemented describing the wavelength dependent CO2 gas absorption to emulate the real application. We were able to conclude that theuse of the silicon microlenses plus the anti-reflective coating and the bouncing pixel can potentially bring the SNR of the system closer to that of the photodetector, for the whole input range of currents, since the sensitivity is kept very high. For the idealized system, very smallchanges in the CO2 gas concentration could be detected, exemplifying the achievable performance of such system.